APACHE II SCORING SYSTEM AND ITS MODIFICATION FOR THE ASSESSMENT OF DISEASE SEVERITY IN CHILDREN WHO UNDERWENT POLYCHEMOTHERAPY - А. V. Sotnikov; V. G. Polyakov; А. I. Saltanov (Сибирский онкологический журнал, 2016)
Short-term disease prognosis should be considered for the appropriate treatment policy based on the assessment of disease severity in patients with acute disease. The adequate assessment of disease severity and prognosis allows the indications for transferring patients to the resuscitation and intensive care department to be defined more precisely. Disease severity of patients who underwent polychemotherapy was assessed using APACHE II scoring system.